2014
DOI: 10.1016/j.antiviral.2014.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotides designed to inhibit TLR9 block Herpes simplex virus type 1 infection at multiple steps

Abstract: Herpes simplex virus type 1 (HSV-1) is an important human pathogen which requires activation of nuclear factor–kappa B (NFκB) during its replication cycle. The persistent nature of HSV-1 infection, and the emergence of drug-resistant strains, highlights the importance of research to develop new antiviral agents. Toll-like receptors (TLR) play a prominent role during the early antiviral response by recognizing viral nucleic acid and gene products, activating NFκB, and stimulating the production of inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…Additionally, treatment with CpG-ODN containing unmethylated CpG provides protection against lethal vaginal challenge with HSV that was probably mediated by an intricate crosstalk between plasmacytoid DCs (pDCs) and vaginal stromal cells, as well as type-I IFNs [ 104 106 ]. Similar to the findings described with TLR3 and TLR7, these results suggest that modulating TLR9 signaling could be a promising strategy for limiting HSV infection in the host, although results from another group suggest that the antiviral effects mediated by TLR9 antagonists might not necessarily be mediated uniquely by intracellular events linked to TLR9 signaling [ 107 ]. Nevertheless, the results obtained with TLR9 agonists suggest that activating this TLR might be a useful strategy for controlling pathological responses induced by HSVs [ 108 ].…”
Section: Evasion Of Hsv Sensing By Host Receptorssupporting
confidence: 65%
“…Additionally, treatment with CpG-ODN containing unmethylated CpG provides protection against lethal vaginal challenge with HSV that was probably mediated by an intricate crosstalk between plasmacytoid DCs (pDCs) and vaginal stromal cells, as well as type-I IFNs [ 104 106 ]. Similar to the findings described with TLR3 and TLR7, these results suggest that modulating TLR9 signaling could be a promising strategy for limiting HSV infection in the host, although results from another group suggest that the antiviral effects mediated by TLR9 antagonists might not necessarily be mediated uniquely by intracellular events linked to TLR9 signaling [ 107 ]. Nevertheless, the results obtained with TLR9 agonists suggest that activating this TLR might be a useful strategy for controlling pathological responses induced by HSVs [ 108 ].…”
Section: Evasion Of Hsv Sensing By Host Receptorssupporting
confidence: 65%
“…3) [4,43,77]. In vitro studies have shown that inhibition of TLR9 using oligonucleotides prevented expression of essential immediate early herpes gene products, and as a result also reduced NFκB activity in nuclear extracts [90]. In the absence of TLR9, other compensatory mechanisms are involved in producing both type I interferon and cytokines, showing that TLR9 only partially contributes to the response against the virus [46,55].…”
Section: Virus-induced Inflammationmentioning
confidence: 99%
“…For example, treatment with a five adjacent guanosine residues (G‐ODN) at a concentration of 10 to 20 μM 2 hours before infection inhibited TLR9 signaling, NF‐κB activity and substantially reduced the yield of lytic virus (90%) in herpes‐susceptible cells. Also, the TLR9 inhibitory effect of CpG oligonucleotide was associated with downregulation of crucial immediate early HSV proteins, impaired viral attachment and entry, virucide activity and mitigated virus replication . Equally, an additional study using both agonists (TLR 3/9) and inhibitors (TLR9) of TLRs demonstrated an increased survival rate of mice when agonists of TLR3 polyinosinic: polycytidylic acid (PIC) and TLR9 (type B ODN 1826) were administered intranasally prior to HSV1 infection.…”
Section: Tlr‐based Therapeutic Opportunities For Hsvmentioning
confidence: 99%